ANNUAL CONFERENCE OF THE FACULTY OF GEOGRAPHY – ENVIRONMENT AT CROSSROADS: SMART APPROACHES FOR A SUSTAINABLE FUTURE – ECOSMART NOVEMBER 17-18, 2023 (Annals of the University of Bucharest. Geography Series, 2024)
The International Conference “Environment at CrossrOads: SMART approaches for a sustainable future – ECOSMART”, took place between November 17-18, 2023 in Bucharest, Romania. The event represents the annual conference of the Faculty of Geography (University of Bucharest), being organized in 2023 by the Department of Regional Geography and Environment as the third iteration of the ECOSMART conference, being previously held in 2015 and 2019.